2020
DOI: 10.1371/journal.pone.0236336
|View full text |Cite
|
Sign up to set email alerts
|

Detection of latent forms of Mycobacterium avium subsp. paratuberculosis infection using host biomarker-based ELISAs greatly improves paratuberculosis diagnostic sensitivity

Abstract: Bovine paratuberculosis (PTB) is a chronic granulomatous enteritis, caused by Mycobacterium avium subsp. paratuberculosis (MAP), responsible for important economic losses in the dairy industry. Current diagnostic methods have low sensitivities for detection of latent forms of MAP infection, defined by focal granulomatous lesions and scarce humoral response or MAP presence. In contrast, patent infections correspond to multifocal and diffuse types of enteritis where there is increased antibody production, and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 60 publications
0
41
1
Order By: Relevance
“…The AUC values calculated for VOC analysis in fecal headspace of individual cattle indicate that this approach has higher discriminatory power than established indirect antibody ELISAs for the identification of MAP-infected animals, where AUC values of 0.55–0.57 [ 32 ] or 0.77–0.91 [ 33 ] were calculated, depending on the reference method used. It is also superior to recently published novel biomarker-based diagnostic tests for paratuberculosis (ABCA13-based ELISA, SPARC ELISA, MMP8 ELISA) with AUC values of 0.79–0.85 [ 34 ]. However, these are only preliminary data, which have to be confirmed in future field studies covering larger numbers of animals and herds.…”
Section: Discussionmentioning
confidence: 99%
“…The AUC values calculated for VOC analysis in fecal headspace of individual cattle indicate that this approach has higher discriminatory power than established indirect antibody ELISAs for the identification of MAP-infected animals, where AUC values of 0.55–0.57 [ 32 ] or 0.77–0.91 [ 33 ] were calculated, depending on the reference method used. It is also superior to recently published novel biomarker-based diagnostic tests for paratuberculosis (ABCA13-based ELISA, SPARC ELISA, MMP8 ELISA) with AUC values of 0.79–0.85 [ 34 ]. However, these are only preliminary data, which have to be confirmed in future field studies covering larger numbers of animals and herds.…”
Section: Discussionmentioning
confidence: 99%
“…Third, most subclinically infected animals typically shed bacteria intermittently, which leads to false-negative results ( 15 ). Enzyme-linked immunosorbent assay (ELISA) is generally easy to conduct with a simple protocol and high-throughput method for herd-level diagnosis ( 16 ). However, diagnosis of MAP-infected cattle at subclinical stage is hampered by the low sensitivity of currently developed commercial ELISA.…”
Section: Introductionmentioning
confidence: 99%
“…Biomarkers are measurable indicators that represent physiological alterations during disease progression. A number of studies have previously identified potential biomarkers in MAP-infected animals ( 16 , 19 , 20 ). Acute phase proteins such as haptoglobin and serum amyloid A were significantly increased in various stages of paratuberculosis infection with different types of lesions ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…used host biomarker-based ELISA to improve the diagnostic sensitivity of Mycobacterium avium subsp. paratuberculosis infection in cattle [33]. Furthermore, recently Gwenin et al fabricated (a) a label free colorimetric assay for active botulinum neurotoxin using soluble N-ethylmaleimide-sensitive attachment protein receptor (SNARE) proteins (SNAP-25) conjugated gold nanoparticles [34], (b) a biosensor over gold working electrode for the detection of active botulinum neurotoxin in a real pharmaceutical sample using EIS [16], (c) SNAP-25 and vesicle associated membrane protein (VAMP) based EIS biosensors over a gold working electrode for detecting the activity of five botulinum neurotoxin serotypes (A-E) [17], and (d) a lateral flow device for the detection of sepsis pathogens using recombinase polymerase amplification [35].…”
Section: Introductionmentioning
confidence: 99%